Analisis Glimepirida Dalam Plasma Tikus - Harahap, Yahdiana; Mansur, Umar; Sinandang, Theresia (UI Scholars Hub, 2006)
The aim of this research is to find the method for analyze glimepiride and itÂ’s metabolite. Glimepiride is the second generation of antidiabetic oral from the sulphonyl urea that works by stimulating the insulin secretion from beta cells of pancreas. Glimepiride is isolated from plasma the using chloroform. Using the high performance liquid chromatography method which include C18 reversed phase column, using mixture of methanol:water (50:50, v/v) as a mobile phase, flow rate 1.0 ml/minutes, detection at wavelenght 228 nm with photo diode array detector gives retention times of glimepiride in 17 minutes without any interference from endogen component of plasma and from itÂ’s metabolite. Linearity with added internal standard gliclazide was established for the range concentration 100-1000 ng/ml with coefficient of correlation (r) is 0.9977 and give the limit of quantitation of glimepiride in 50 ng/ml. The results of validation method fulfilled for the given criterias.